Understanding the impact of work environment on employee well-being and cynicism: Insights from the hotel industry - Ahmed MAGDY; Islam Elbayoumi SALEM (Tourism and Hospitality Management)
Purpose – The paper aims to deepen the understanding of various psychological and sociological theories that contend that people prefer to work in a healthy environment that provide favorable working conditions, such as affective events theory, well-being theory, leadership theory, and organizational support theory. Therefore, if the hospitality sector does not provide appropriate working conditions and does not support psychological wellbeing, it might be difficult to find motivated and devoted employees. Methodology/Design/Approach – The study used a self-administered questionnaire and opted for a descriptive-analytical design. Typically, the interviewer or a representative from an official position hands out this kind of questionnaire to the interviewees. The researcher contacted 396 front-line staff members at five-star hotels belonging to a chain in the most popular tourist areas in Egypt. The data were analysed using the Smart PLS statistical program to test the study hypotheses. Findings – The paper provides insights into how toxic leadership negatively influences employee wellbeing and positively influences behavioural cynicism. In addition, employee silence significantly moderates the relationship concerning toxic leadership and employees’ outcomes (wellbeing and behavioural cynicism). These results raise a number of theoretical and practical implications for hospitality practitioners. Originality of the research – This paper fulfils an identified need to study various psychological and sociological theories in the hospitality context to give more understanding of how employee silence maximizes the negative consequences upon wellbeing. Furthermore, justifies employees’ behavioural cynicism as a sign of indulging in a toxic leadership. Additionally, in the academic literature on hospitality, this study is one of the very few that investigated behavioural cynicism consequences and considered employee silence as a moderator.